Politics, power and pathologies of international organizations - Barnett, Michael N. (1999)
Develops a constructivist approach rooted in sociological institutionalism to explain both the power of international organizations (IOs) and their propensity for dysfunctional, even pathological behaviour. Argues that the rational-legal authority that IOs embody gives them power independent of the states that created them and channels that power in particular directions.